(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
Maladministration in tax services remains a significant challenge to legal certainty and the protection of taxpayers’ rights in Indonesia, particularly within the rapid transition to digital taxation. This study examines the evolution of digital tax maladministration, culminating in the early 2025 implementation of the Coretax Administration System, which has sparked new operational issues such as system incompetence, procedural bugs, and server inaccessibility. Analyzing statistical trends from the Ombudsman of the Republic of Indonesia from 2023 to 2025, this research evaluates how technical failures unjustly impose administrative and financial penalties on taxpayers without any fault on their part. Using a normative legal research method with statutory, conceptual, and case approaches, this study analyzes the construction of government liability and the effectiveness of available legal remedies. The findings reveal that digital service failures (service failures) constitute a public authority tort (onrechtmatige overheidsdaad) under the category of faute de service. Consequently, the Directorate General of Taxes administrative responsibility to restore taxpayers’ rights through correction, cancellation of unlawful administrative sanctions, and other administrative remedies in accordance with Indonesian administrative law. To ensure robust legal protection, this study recommends the formalization of a preventive "tax digital disaster protocol" via Ministerial Regulation and emphasizes the crucial repressive synergy between the Ombudsman RI and the Administrative Court (PTUN).